2020
DOI: 10.1017/sjp.2020.26
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Validation and Scoring of the Internet Gaming Disorder Scale - Short-Form (IGDS9-SF)

Abstract: Since the inclusion of the Internet Gaming Disorder (IGD) in the Diagnostic and statistical manual of mental disorders (5th ed.) (DSM-5), the Internet Gaming Disorder Scale-Short Form (IGDS9-SF), a short nine items test, has become one of the most used standardized instruments for its psychometric evaluation. This study presents a validation and psychometric evaluation of the Spanish version of the IGDS9-SF. A sample of 2173 videogame players between 12 and 22 years old, comprising both genders, was employed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
1
8
0
4
Order By: Relevance
“…Finally, the average value on the IGDS9-SF, 13.51, is low and only 3 out of the 1228 women (.02%) and out of the 626 who played VG (.47%) exceeded the cut-off score of 36 points suggested by Pontes & Griffith (2015), whereas the percentage rises to 1.7% if 27 is used as cut-off. As it was expected the scores found in this sample of women are below those of men, suggesting less problems with the use of VG (Rehbein et al, 2016;Sánchez-Iglesias et al, 2020). In the study of Witteck et al, (2016) men were found to be 2.9 times more likely to have problems with VG than women; in the study of Bonnaire and Baptista (2019), almost 4 times more.…”
Section: Discussionsupporting
confidence: 47%
“…Finally, the average value on the IGDS9-SF, 13.51, is low and only 3 out of the 1228 women (.02%) and out of the 626 who played VG (.47%) exceeded the cut-off score of 36 points suggested by Pontes & Griffith (2015), whereas the percentage rises to 1.7% if 27 is used as cut-off. As it was expected the scores found in this sample of women are below those of men, suggesting less problems with the use of VG (Rehbein et al, 2016;Sánchez-Iglesias et al, 2020). In the study of Witteck et al, (2016) men were found to be 2.9 times more likely to have problems with VG than women; in the study of Bonnaire and Baptista (2019), almost 4 times more.…”
Section: Discussionsupporting
confidence: 47%
“…Taking together, the results on the validity and reliability allow us to conclude that the Spanish GDT is an adequate psychometric test to assess GD within the Spanish population, reaching similar promising results than those found with the Spanish version of the Spanish IGDS9-SF (Beranuy et al, 2020 ; Maldonado-Murciano et al, 2020 ; Sánchez-Iglesias et al, 2020 ). Since the Spanish IGDS9-SF assesses disordered gaming under the APA framework, the present Spanish GDT represents a better assessment option for health professionals and clinicians alike when conducting assessment of disordered gaming adopting the WHO framework.…”
Section: Discussionmentioning
confidence: 54%
“…The IGDS9-SF has been shown to present with robust psychometric properties according to a recent review study of 21 studies across 15 languages that employed the IGSD9-SF (Poon et al, 2021 ). Spanish IGDS9-SF has been found to present with excellent psychometric properties under the CTT (Beranuy et al, 2020 ; Sánchez-Iglesias et al, 2020 ) and IRT frameworks (Maldonado-Murciano et al, 2020 ). In the present study, the IGDS9-SF exhibited high levels of internal consistency ( α = 0.90 and ω = 0.85).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current literature, the IGDS9-SF has been translated into 17 languages: Chinese, with three sublanguages of traditional Chinese in Hong Kong [22][23][24], traditional Chinese in Taiwan [22][23][24], and simplified Chinese in mainland China [25]; Albanian [26]; Italian [26]; English [26]; European and South American Portuguese [27,28]; Slovenian [29]; Persian [30]; Polish [31]; Spanish [32][33][34]; Turkish [35]; German [36]; Czech [37]; Malay [38]; and Korean [39]. As a screening tool, the IGDS9-SF can help clinicians in assessing IGD severity and the detrimental health impacts on the individual's life with reasonable accuracy in a time-efficient way.…”
Section: Introductionmentioning
confidence: 99%